Pengaruh Profitabilitas, Tunneling Incentive, dan Intangible Asset Terhadap Transfer Pricing Perusahaan Manufaktur - Uzma, Salsa Raehan; Budiantara, Martinus (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Transfer pricing remains a critical issue in accounting and taxation practices, particularly in multinational companies, due to its potential for tax avoidance. This study aims to determine the effect of profitability, tunneling incentives, and intangible assets on transfer pricing in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX). The data used are secondary data obtained from annual financial reports for the 2022–2024 period. The study population consisted of 95 companies, and through purposive sampling, 19 companies met the criteria, with a total of 57 observations. Data analysis was performed using multiple linear regression to examine the effect of each independent variable on transfer pricing. The results of the study indicate that profitability and intangible assets have no effect on transfer pricing with significance values ​​of 0.090 > 0.05 and 0.323 > 0.05, respectively. While tunneling incentives have a significant negative effect on transfer pricing with a value of 0.046 < 0.05. This study is expected to contribute to the financial accounting literature related to transfer pricing practices and become a consideration for regulators in formulating tax policies in Indonesia.